Pain modulated by Bothrops snake venoms: Mechanisms of nociceptive signaling and therapeutic perspectives - Cavalcante, Joeliton dos Santos [UNESP]; Nogueira Júnior, Francisco Assis; Bezerra Jorge, Roberta Jeane; Almeida, Cayo (Elsevier, 2021)
Snake venoms are substances mostly composed by proteins and peptides with high biological activity. Local and systemic effects culminate in clinical manifestations induced by these substances. Pain is the most uncomfortable condition, but it has not been well investigated. This review discusses Bothrops snakebite-induced nociception, highlighting molecules involved in the mediation of this process and perspectives in treatment of pain induced by Bothrops snake venoms (B. alternatus, B. asper, B. atrox, B. insularis, B. jararaca, B. pirajai, B. jararacussu, B. lanceolatus, B. leucurus, B. mattogrossensis, B. moojeni). We highlight, the understanding of the nociceptive signaling, especially in snakebite, enables more efficient treatment approaches. Finally, future perspectives for pain treatment concerning snakebite patients are discussed.
Keywords: Bothrops; Inflammation; Nociception; Snakebite; Tissue damage